Effectiveness of total quality management intervention on nursing job performance and commitment in government hospitals in Irbid, Jordan - Al Zoubi, Majdi Musa Mohammad (2019)
Background: There is a consensus among hospitals management, health professionals, and policy makers that hospitals and nursing services from the government hospitals are lagging behind in terms of performance and good commitment due to their nurse’s poor performance, and several studies have cited this current problem in Jordan. Total Quality Management implementation helps hospitals to identify and eliminate areas generating the most waste and to improve department workflows, thereby increasing overall service quality by using the strategies for quality improvement.